2022
DOI: 10.1097/md.0000000000030347
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on efficacy and safety of rituximab for neuromyelitis optica spectrum disorders

Abstract: Background: To assess the efficacy and safety of rituximab (RTX) in the treatment of neuromyelitis optica spectrum diseases (NMOSDs), and give a guideline on clinical medication Methods: The databases of Pubmed, Embase, Cochrane Library, CNKI, and Wan fang were systematically searched by computer, and the search period was from the establishment of the databases until January 2022. To collect the trials of RTX in the treatment of NMOSDs, two researchers completed literature screening, quality assessment, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Rituximab is a chimeric monoclonal antibody that binds to and depletes CD20-positive B-cells. Its clinical effectiveness in NMOSD has been demonstrated in various retrospective and prospective studies, including AQP4-IgG-positive and -negative (adult and pediatric) patients, with a reduction of attack rates by over 80% [ 52 , 53 , 61 , 74 , 135 , 253 ]. A recent randomized, double-blinded, placebo-controlled trial from Japan (RIN-1) confirmed the efficacy of rituximab in AQP4-IgG-positive NMOSD, although the sample size of the trial was small (Table 2 ) ([ 216 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Rituximab is a chimeric monoclonal antibody that binds to and depletes CD20-positive B-cells. Its clinical effectiveness in NMOSD has been demonstrated in various retrospective and prospective studies, including AQP4-IgG-positive and -negative (adult and pediatric) patients, with a reduction of attack rates by over 80% [ 52 , 53 , 61 , 74 , 135 , 253 ]. A recent randomized, double-blinded, placebo-controlled trial from Japan (RIN-1) confirmed the efficacy of rituximab in AQP4-IgG-positive NMOSD, although the sample size of the trial was small (Table 2 ) ([ 216 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%